The Relationship Between Tumor Necrosis Factor-Alpha (TNF-α) with Retinal Nerve Fiber Layer (RNFL) Thickness in Diabetic Retinopathy Patients at Prof. CPL Universitas Sumatera Utara General Hospital and Affiliated Hospital - Putra, Wahyu Medsa Yeltas; Delfi; Ashar, Taufik (Majalah Oftalmologi Indonesia, 2025)
Introduction: Retinal neurodegeneration may be an early indicator of diabetic retinopathy, the second most common complication after nephropathy. Tumor Necrosis Factor-Alpha (TNF-α) plays a role in the pathogenesis of inflammatory and neovascular eye disorders and is associated with intraocular inflammatory diseases like macular edema and proliferative diabetic retinopathy. This study aims to find the relationship between TNF-α levels and Retinal Nerve Fiber Layer (RNFL) thickness in diabetic retinopathy patients at Prof. CPL Universitas Sumatera Utara General Hospital and affiliated hospital.   Methods: This cross-sectional study included 45 patients with type 2 DM and diabetic retinopathy at Prof. CPL Universitas Sumatera Utara General Hospital and affiliated hospital from March to June 2024. RNFL and posterior segment examinations were conducted. TNF-α levels were measured from blood samples.Blood sugar data were taken from medical records.   Results: Of the 45 participants, 24 were men (53.3%) and 21 women (46.7%). 32 (71.1%) had DM for >5 years, and 27 (60%) experienced PDR. Highest location for RNFL thickness examination was superior (19, 42.2%). Average TNF-α with thin RNFL was 65.67 ng/L, and with thick RNFL was 64.78 ng/L. Mean TNF-α with thin superior RNFL was 65.74 ng/L, and thick was 63.70 ng/L. Mean TNF-α with thin inferior RNFL was 65.73 ng/L, and thick was 63.9 ng/L. Mean TNF-α with thin temporal RNFL was 68.73 ng/L, and thick was 67.19 ng/L. Mean TNF-α with thick nasal RNFL was 67.06 ng/L.   Conclusion: There was no statistically significant relationship between TNF-α and RNFL thickness in diabetic retinopathy patients.